Clinical Longevity of Sonicated and Unsonicated Composite Resin Restorations in Posterior Permanent Teeth: A Systematic Review and Meta-Analysis - Lorrane Salvador de Mello; Fabiola Fontes Galdino; Jayzon Stephan Brooks; Tatiana Kelly da Silva Fidalgo; Kátia Rodrigues Reis (Association of Support to Oral Health Research (APESB), 2024)
Objective: To evaluate the clinical longevity of Class I and II composite resin restorations with and without using sonic energy through a systematic literature review and meta-analysis. Material and Methods: Five databases were consulted: PubMed, Cochrane Library, Web of Science, Scopus, VHL-LILACS, and BBO and gray literature. The search was carried out in January 2024. The inclusion criteria comprised clinical trials evaluating the success/longevity of composite resin restorations with and without sonic energy. RoB and ROBINS-I assessed the risk of bias. The meta-analysis analyzed the number of restorations with alpha USPHS scores. Heterogeneity was assessed (I² index, p<0.05). Certain evidence was assessed using the GRADE tool. Results: A total of 8,582 studies were identified, including four studies, 2 RCTs, and two controlled clinical trials, with moderate and low risk of bias, respectively. No difference was observed in the longevity (p>0.05) for: anatomical shape (CI=1.05 [0.95,1.15]; I²=0%; p=0.37); color stability (CI=1.02 [0.93,1.13; I²=0%, p=0.65); marginal adaptation (CI=1.05 [0.95,1.16]; I²=%; p=0.38); postoperative sensitivity (CI=1.01 [0.93,1.10]; I²=0%; p=0.80); secondary caries (CI=1.01 [0.93,1.10]; I²=0%; p=0.80); marginal discoloration (CI=1.05 [0.95,1.16]; I²=0%; p=0.38), surface texture (CI=1.09 [0.97,1.23]; I²=19%; p=0.14) and retention (CI=1.00 [1.91,1.10]; I²=0%; p=1.00). The certainty of the evidence was very low. Conclusion: No evidence supports using sonic energy for direct composite resin restorations, regardless of the technique and the restored tooth. More robust and well-conducted studies should be performed.